Online-based activities to improve students’ critical thinking, problem solving, and communication - Marinu Waruwu; Yari Dwikurnaningsih; Sophia Tri Satyawati (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study aimed to explain how students’ critical thinking, problem solving and communication skills can be developed through student development activities in online-based scientific discussion programs at universities. This study used a mix method approach with a sequential explanatory model. The research was conducted using quantitative methods in the first stage and then in the second stage using qualitative methods. Management discussion model was measured through questionnaires and interviews. The quantitative data analysis was employed to identify the effectiveness of the discussion model and its impact. The qualitative data analysis was carried out in three stages, namely data reduction, data presentation; and drawing conclusions. The research findings showed that the model of student development activities with online-based scientific discussion methods can significantly improve students’ critical thinking, problem solving, and communication skills. The results of this study indicated that universities provide opportunities for students to improve critical thinking skills, problem solving and communication skills through online-based scientific discussion programs.